Opioid-sparing anesthesia versus opioid-free anesthesia for postoperative recovery quality in breast cancer surgery patients: A systematic review and Bayesian network meta-analysis - JingWang Liu; JiaXin Liu; Mingjie Wang; Xiuli Wang (PLoS ONE, 2025)
Background Breast cancer is the most common malignancy among women, and patients require rapid transition to adjuvant therapy post-surgery. Opioid-based anesthesia (OBA) is widely used but carries risks such as postoperative nausea and vomiting (PONV), immunosuppression, and hyperalgesia, which may delay recovery. Opioid-sparing anesthesia (OSA) and opioid-free anesthesia (OFA) may reduce these risks, but their effects on postoperative quality of recovery (QoR) are unclear. This study compares the effects of these three anesthetic strategies on early postoperative QoR in breast cancer surgery using a Bayesian network meta-analysis. Methods Following PRISMA guidelines (PROSPERO ID: CRD420251065588), a systematic search was conducted in PubMed, Cochrane Library, EMBASE, and Web of Science from inception to June 1, 2025. Included were randomized controlled trials (RCTs) comparing OSA, OFA, and OBA in adult breast cancer surgery that reported QoR scores. Risk of bias and evidence quality were assessed using the Cochrane tool and GRADE system. Bayesian random-effects analysis was performed with the R package gemtc . Continuous data were reported as mean differences, and categorical data as odds ratios. Results Seventeen RCTs with 1,254 patients were included. Bayesian network meta-analysis showed that OSA significantly outperformed OBA in 24-hour postoperative QoR (d = 0.050, 95% CrI: 0.038–0.062; SUCRA = 85.3%), and OFA was also superior to OBA (d = 0.044, 95% CrI: 0.020–0.068; SUCRA = 64.7%). No significant difference was found between OSA and OFA (d = −0.006, 95% CrI: −0.029–0.018). Secondary outcomes SUCRA showed that OFA was most effective in controlling postoperative nausea and vomiting (99.4%) and pain management (81.4%), while OSA excelled in emotional well-being (96.2%) and physical comfort (76.6%). For physical independence, OFA (85.1%) outperformed OSA (63.5%), with no differences in psychological support. Intraoperative opioid reduction showed an inverted U-shaped relationship with QoR improvement (p = 0.0004). Conclusion OSA is the optimal strategy for enhancing overall quality of recovery within 24 hours after breast cancer surgery. Although OFA excels in PONV reduction and pain control, OSA offers more balanced benefits across multiple QoR dimensions. An individualized anesthetic approach is recommended, aiming for opioid minimization rather than complete elimination.